2016
DOI: 10.1038/srep38214
|View full text |Cite
|
Sign up to set email alerts
|

A indicator of visceral adipose dysfunction to evaluate metabolic health in adult Chinese

Abstract: Visceral adipose dysfunction is a major cause of metabolic disorders. However, there is lack of a clinical index for prediction of visceral fat dysfunction in Asians. The present study aims to establish a visceral adiposity index for evaluation of metabolic health status in Chinese, the largest Asian ethnic group. 485 subjects were recruited from Lianqian Community, Xiamen and received abdominal computed tomography(CT) for visceral fat area. A Chinese visceral adiposity index (CVAI) was created using multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
202
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 152 publications
(215 citation statements)
references
References 40 publications
9
202
4
Order By: Relevance
“…A CVAI was recently established to estimate the visceral adipose area . The current prospective study further showed that CVAI could be used as a simple clinical index for visceral adiposity to predict the risks of prediabetes and diabetes irrespective of age, gender, obesity, metabolic syndrome, or its components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A CVAI was recently established to estimate the visceral adipose area . The current prospective study further showed that CVAI could be used as a simple clinical index for visceral adiposity to predict the risks of prediabetes and diabetes irrespective of age, gender, obesity, metabolic syndrome, or its components.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that visceral fat area estimated by CVAI had a better prediction value than other traditional estimates of obesity for the prediction of incident prediabetes and diabetes. Importantly, the CVAI is mainly composed of the components of metabolic syndrome (BMI, waist circumference, serum TG, and HDL‐c), which are easily available in clinical practice . Age was also included as a covariate in CVAI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PBF was calculated as the total mass of fat divided by total body mass. VFI is a novel and accurate and reliable indicator for assessing body fat stored around important internal organs, which is significantly associated with many health‐related outcomes, such as prehypertension, adipose tissue dysfunction, and type 2 diabetes . Bioimpedance analysis is a measurement technique based on electrophysiological characteristics of the dielectric and conductive properties of human tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Dual‐energy X‐ray absorptiometry scanning (Lunar iDXA, GE, USA) was applied for assessing lean body mass and fat mass in all subjects. Besides, Chinese visceral adiposity index (CVAI), a reliable index for evaluation of visceral adiposity area in Chinese, was calculated as follows: For males: CVAI = −267.93 + 0.68 × age (years) + 0.03 × BMI (kg/m 2 ) + 4.00 × waist circumference (cm) + 22.00 × Log10TG (mmol/L) − 16.32 × HDL‐C (mmol/L). For females: CVAI = −187.32 + 1.71 × age (years) + 4.23 × BMI (kg/m 2 ) + 1.12 × waist circumference (cm) + 39.76 × Log10TG (mmol/L) − 11.66 × HDL‐C (mmol/L). …”
Section: Methodsmentioning
confidence: 99%